Serial comprehensive geriatric assessment in elderly head and neck cancer patients undergoing curative radiotherapy identifies evolution of multidimensional health problems and is indicative of quality of life. (28th January 2014) - Pottel, L.; Lycke, M.; Boterberg, T.; Pottel, H.; Goethals, L.; Duprez, F.; Van Den Noortgate, N.; De Neve, W.; Rottey, S.; Geldhof, K.; Buyse, V.; Kargar‐Samani, K.; et al.
<x xml:space="preserve">Abstract</x> Head and neck (H&N) cancer is mainly a cancer of the elderly; however, the implementation of comprehensive geriatric assessment (CGA) to quantify functional age in these patients has not yet been studied. We evaluated the diagnostic performance of screening tools [Vulnerable Elders Survey‐13 (VES‐13), G8 and the Combined Screening Tool 'VES‐13 + (17‐G8)' or CST], the feasibility of serial CGA, and correlations with health‐related quality of life evolution [HRQOL; European Organisation for Research and Treatment of Cancer Quality of Life Questionnaires (EORTC QLQ)‐C30 and ‐HN35] during therapy in hundred patients, aged ≥65 years, with primary H&N cancer undergoing curative radio(chemo)therapy. Respectively 36.8%, 69.0%, 62.1% and 71.3% were defined vulnerable according to VES‐13, G8, CST and CGA at week 0, mostly due to presence of severe grade co‐morbidities, difficulties in community functioning and nutritional problems. At week 4, significantly more patients were identified vulnerable due to nutritional, functional and emotional deterioration. The CST did not achieve the predefined proportion necessary for validation. Vulnerable patients reported lower function and higher symptom HRQOL scores as compared with fit patients. A comparable deterioration in HRQOL was observed in both groups through therapy. In conclusion, G8 remains the screening tool of choice. Serial CGA identifies the evolution of multidimensional health problems and HRQOL conditions during therapy with potential to guide individualised supportive care.